2011
DOI: 10.1097/mlr.0b013e318207ef87
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcomes for Congestive Heart Failure by Race/Ethnicity in TRICARE

Abstract: This study suggests that although there are some racial and ethnic disparities in the receipt of pharmacological therapy for CHF among TRICARE beneficiaries, these differences do not translate into disparities in the likelihood of a PAH. The findings support previous research suggesting that equal access to care may mitigate racial/ethnic health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…As a claims-based registry, we recognize that we do not have any information on radiographic findings, severity of disease, disability or pain scores, or procedural rationale. However, there is no evidence to support the contention that the rationale for surgical intervention or approaches to care differs between the fee-for-service and direct care settings [3,18,22]. Lastly, other than documenting differences in procedural selection between fee-for-service and salaried surgeons, we cannot truly elucidate their underlying motivations.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…As a claims-based registry, we recognize that we do not have any information on radiographic findings, severity of disease, disability or pain scores, or procedural rationale. However, there is no evidence to support the contention that the rationale for surgical intervention or approaches to care differs between the fee-for-service and direct care settings [3,18,22]. Lastly, other than documenting differences in procedural selection between fee-for-service and salaried surgeons, we cannot truly elucidate their underlying motivations.…”
Section: Discussionmentioning
confidence: 89%
“…The MDR captures all information on inpatient and outpatient insurance claims handled through TRICARE irrespective of the environment of care or the location of service. TRICARE data have previously been utilized in other initiatives evaluating the delivery of surgical services in a number of different contexts [3,18,22]. Moreover, the broad demographic insured through TRICARE, which covers individuals of extremely varied sociodemographic, educational, professional, and vocational backgrounds, has been considered representative of the American population aged 18 to 64 years in prior studies [3,16,18,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, risk factor modification can be challenging, especially when the targeted community is either uninsured or lacks the necessary resources (Rodriguez et al, 2011). Bagchi et al (2011) suggested that equal access to care may mitigate health disparities among the varying ethnic HF patients. Historically, minority groups have faced challenges in accessing health care.…”
Section: Introductionmentioning
confidence: 99%